Influence of changes in hip bone morphology and anterior knee pain - Sanchez, Hugo Machado; Castro, Layla Rosa de; Borges, Beatriz Santana; Sanchez, Eliane Gouveia de Morais; Junior, Jair Pereira de Melo (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The patellofemoral pain syndrome (PFPS) is one of the most common disorders of the knee, and there is still unclear etiology. Objective: The aim of this study was to correlate patellofemoral pain syndrome with the bone morphology of hip. Method: For this, this study evaluated 31 studied volunteers with aged between 18 and 30 years, which analyzed the distance of anterior superior iliac spines (ASIS), asymmetry of the pelvis, lower limb length (LL), distance from the ASIS bilaterally of the patella, lateral tilt and iliac inclination, this by computerized biophotogrammetry. Results: After collecting the data and consequent tabulation, it was found that were no changes in the data collected except in the lateral tilt, so the volunteers who had anterior knee pain also had lateral pelvic tilt. Conclusion: That said, we can infer that there is little relationship between the morphological changes of the hip with the PFPS, whereas found only one was in lateral pelvic tilt voluntary group who complained of pain above the knee.